Evaluación de la contribución al SENCICO de las empresas de construcción en la región San Martín, año 2016 - Del Aguila Gonzáles, Katty Violeta (2020)
The research entitled: “Evaluation of the contribution to SENCICO by construction companies in the San Martín Region, year 2016”, proposes to evaluate the contribution performed by these companies from an accounting, tax and billing point of view. The research is of the applied type, with a descriptive non-experimental level, having as study sample 15 companies classified as main taxpayers of the Tarapoto SUNAT’s zonal office; the survey and technical data analysis were used as research instruments. The results showed that the accounting and tax factors about compliance with the contribution to SENCICO by the construction companies of the San Martín Region for the year 2016, are related to the non-registration or billing of all the activities they carry out, where the level of compliance accounting is 68.8% and tax is 61.2%; the level of contribution based on their billing is deficient, where 6.7% of the companies do not register their contribution payments for invoices made for subcontracted works; the arrears for contributions represents 10% and 26.6% of the companies have had some penalty fee for omission to contributions to SENCICO. In conclusion, the level of compliance with the contribution to SENCICO of the construction companies of the San Martín Region por the year 2016, is deficient, where 2 out of 10 companies present some indicator of accounting or tax non-compliance of the contribution.